Pengaruh penambahan sulfat terhadap penyisihan logam timbal (Pb) pada reactor biologi anaerob - Bekti Prihatiningsih (Jurnal Penelitian, 2003)
Pb metal can be reduced its presence in wastewater containing high organic matter by using a limited mixed bacterial culture in an anaerobic biological reactor. The process of reducing or removing heavy metals in biological reactors occurs through enzymatic processes such as oxidation-reduction processes and non-enzymatic processes. This research was conducted to examine the effect of sulfate compounds as reducing agents as one of the enzymatic processes in microbiological treatment processes to increase lead (Pb) removal in wastewater using limited mixed bacterial cultures. With the addition of sulfate in the anaerobic reactor, it was found that the removal of Pb was greater than the removal of Pb without the addition of sulfate. The maximum Pb removal obtained was 4.53 mg/l/day with the addition of 10 mg/l sulfates with an initial Pb concentration of 77.63 mg/l and a minimum of 0.45 mg/l/day with the addition of 5 mg/l sulfates. with the initial concentration of Pb 13,33 mg/l.